Synthesis and Characterisation of Divalent Metal Complexes Derived from Phenytoin Sodium. - SINGH, PRAMILA; KESHARWANI., RACHNA (Asian Journal of Chemistry, 2010)
In the present work, we report the synthesis and charactcrization of the complexes ML2X2 [M = Co(II), Ni(II) and Cu(II), L = Phenytoin (5,5-diphenyl-2, 4-imadazolidinedione) and X = H2O]. Octahedral environment around each metal is proposed by axial coordination of two water molecules.